An improved region-based embedding technique for data hiding and image recovery using multiple ROI and RONI. (9th January 2023) - Paikaray, Bijay Kumar; Swain, Debabala; Chakravarty, Sujata
To preserve the sensitive contents of digital images during their transmission, it is essential to hide them with maximum imperceptibility so that intruders will not be able to identify them visually. The image recovery at the receiver end is equally significant because of sensitive images, like medical diagnosis images, satellite images, etc. This paper proposes an improved image hiding technique where the sensitive contents of the image are located in multiple regions. These regions get embedded based on histogram analysis of the region of interest (ROI) pixels then hidden in the region of non-interest (RONI). Further, the reverse operations can be applied to the embedded regions and the hidden data are retrieved from RONI. Using this technique, the embedded regions can be easily extracted, recovered, and fully restored without any loss in data. The proposed work is on multiple ROI with the reliability, integrity, and confidentiality of transmitted images.